SUMOylation of the Hyperpolarization-Activated Cyclic Nucleotide-Gated Channel 2 Increases Surface Expression and the Maximal Conductance of the Hyperpolarization-Activated Current - Parker, Anna R.; Welch, Meghyn A.; Forster, Lori A.; Tasneem, Sarah M.; Dubhashi, Janhavi A.; Baro, Deborah J. (Frontiers in Molecular Neuroscience, 2017)
Small Ubiquitin-like Modifier (SUMO) is a ~10kDa peptide that can be post-translationally added to a lysine (K) on a target protein to facilitate protein-protein interactions. Recent studies have found that SUMOylation can be regulated in an activity-dependent manner and that ion channel SUMOylation can alter the biophysical properties and surface expression of the channel. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channel surface expression can be regulated in an activity-dependent manner through unknown processes. We hypothesized that SUMOylation might influence the surface expression of HCN2 channels. In this manuscript we show that HCN2 channels are SUMOylated in the mouse brain. Baseline levels of SUMOylation were also observed for a GFP-tagged HCN2 channel stably expressed in Human embryonic kidney (Hek) cells. Elevating GFP-HCN2 channel SUMOylation above baseline in Hek cells led to an increase in surface expression that augmented the hyperpolarization-activated current (Ih) mediated by these channels. Increased SUMOylation did not alter Ih voltage-dependence or kinetics of activation. There are five predicted intracellular SUMOylation sites on HCN2. Site-directed mutagenesis indicated that more than one K on the GFP-HCN2 channel was SUMOylated. Enhancing SUMOylation at one of the five predicted sites, K669, led to the increase in surface expression and Ih Gmax. The role of SUMOylation at additional sites is currently unknown. The SUMOylation site at K669 is also conserved in HCN1 channels. Aberrant SUMOylation has been linked to neurological diseases that also display alterations in HCN1 and HCN2 channel expression, such as seizures and Parkinson’s Disease. This work is the first report that HCN channels can be SUMOylated and that this can regulate surface expression and Ih.